Optimal motion of triangular magnetocapillary swimmers - Sukhov, Alexander; Ziegler, Sebastian; Xie, Qingguang; Trosman, Oleg; Pande, Jayant; Grosjean, Galien; Hubert, Maxime; Vandewalle, Nicolas; Smith, Ana-Suncana; Harting, Jens (Journal of Chemical Physics, 2019)
A system of ferromagnetic particles trapped at a liquid-liquid interface and subjected to a set of magnetic fields (magnetocapillary swimmers) is studied numerically using a hybrid method combining the pseudopotential lattice Boltzmann method and the discrete element method. After investigating the equilibrium properties of a single, two, and three particles at the interface, we demonstrate a controlled motion of the swimmer formed by three particles. It shows a sharp dependence of the average center-of-mass speed on the frequency of the time-dependent external magnetic field. Inspired by experiments on magnetocapillary microswimmers, we interpret the obtained maxima of the swimmer speed by the optimal frequency centered around the characteristic relaxation time of a spherical particle. It is also shown that the frequency corresponding to the maximum speed grows and the maximum average speed decreases with increasing interparticle distances at moderate swimmer sizes. The findings of our lattice Boltzmann simulations are supported by bead-spring model calculations.
CRIS-Team Scopus Importer:2019-10-08